2020
DOI: 10.1002/ese3.762
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of imbibition in tight oil reservoirs from the perspective of physical experiments and theory

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The presence of nanopores in tight sandstones has also been captured in NMR analysis. 16 Lyu et al 27 also revealed 10 nm pores in their study.…”
Section: Methodsmentioning
confidence: 68%
See 3 more Smart Citations
“…The presence of nanopores in tight sandstones has also been captured in NMR analysis. 16 Lyu et al 27 also revealed 10 nm pores in their study.…”
Section: Methodsmentioning
confidence: 68%
“…This confirms the observations in earlier studies that sandstone samples can contain pore sizes as small as nanometers. The presence of nanopores in tight sandstones has also been captured in NMR analysis . Lyu et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations